Effect of cadmium on growth parameters and the development of defence reactions of wheat varieties (Experimental biology, 2016)
The article presents data on the effect of cadmium on growth and biomass accumulation of wheat seedlings, the degree of lipid peroxidation (LPO), proline әль-Фараби атындағы КазҰУ, content and the activity of antioxidant enzymes superoxide dismutase and peroxidase. Kazakhstan-3 and Melturn varieties were more tolerant to cadmium effect and Kazakhstanskaya rannnaya and Shagala varieties were more sensitive. Kayir variety was moderately resistant. Thus, the cadmium effect increased the level of lipid peroxidation. A malondialdehyde content in relatively resistant to these stressors varieties increased to a lesser extent than in sensitive cultivars. Consequently, the level of lipid peroxidation directly correlated with the degree of tolerance of wheat cultivars. It was found that in response to cadmium the content of proline and activity of antioxidant enzymes were increased in wheat cultivars.
Keywords: wheat; cadmium; growth; lipid peroxidation; prolin; superoxide dismutase; peroxidase